Studying Biofilm and Clinical Issues in Orthopedics - Peel, Trisha N. (Frontiers in Microbiology, 2019)
The association between biofilm-forming microorganisms and prosthetic joint infection influences all aspect of management including approaches to diagnosis, management and prevention. This article will provide an overview of new anti-biofilm strategies for management of prosthetic joint infection.